Dental microwear texture analysis correlations in guinea pigs (Cavia porcellus) and sheep (Ovis aries) suggest that dental microwear texture signal consistency is species-specific - Martin, Louise Françoise; Winkler, Daniela Eileen; Ackermans, Nicole Lauren; Müller, Jaqueline; Tütken, Thomas; Kaiser, Thomas; Codron, Daryl; Schulz-Kornas, Ellen; Hatt, Jean-Michel; Clauss, Marcus (Frontiers in Ecology and Evolution, 2022)
Dental microwear texture (DMT) analysis is used to differentiate abrasive dental wear patterns in many species feeding on different diets. Because DMT parameters all describe the same surface, they are expected to correlate with each other distinctively. Here, we explore the data range of, and correlations between, DMT parameters to increase the understanding of how this group of proxies records wear within and between species. The analysis was based on subsets of previously published DMT analyses from guinea pigs, sheep, and rabbits fed either a natural whole plant diet (lucerne, grass, bamboo) or pelleted diets with or without added quartz abrasives (guinea pigs and rabbits: < 45 days, sheep: 17 months). The normalised DMT parameter range (P4: 0.69 ±0.25; M2: 0.83 ±0.16) and correlation coefficients (P4: 0.50 ±0.31; M2: 0.63 ±0.31) increased along the tooth row in guinea pigs, suggesting that strong correlations may be partially explained by data range. A comparison between sheep and guinea pigs revealed a higher DMT data range in sheep (0.93 ±0.16; guinea pigs: 0.47 ±0.29), but this did not translate into more substantial correlation coefficients (sheep: 0.35 ±0.28; guinea pigs: 0.55 ±0.32). Adding rabbits to an interspecies comparison of low abrasive dental wear (pelleted lucerne diet), the softer enamel of the hypselodont species showed a smaller data range for DMT parameters (guinea pigs 0.49 ±0.32, rabbit 0.19 ±0.18, sheep 0.78 ±0.22) but again slightly higher correlations coefficients compared to the hypsodont teeth (guinea pigs 0.55 ±0.31, rabbits 0.56 ±0.30, sheep 0.42 ±0.27). The findings suggest that the softer enamel of fast-replaced ever-growing hypselodont cheek teeth shows a greater inherent wear trace consistency, whereas the harder enamel of permanent and non-replaced enamel of hypsodont ruminant teeth records less coherent wear patterns. Because consistent diets were used across taxa, this effect cannot be ascribed to the random overwriting of individual wear traces on the more durable hypsodont teeth matching literature reports on reduced DMT pattern consistency on harder materials; possibly, individual wear events become more random in nature on harder material. Given species-specific differences in enamel characteristics, the findings suggest a certain species-specificity of DMT patterns.